School Policy in Improving Discipline Character of Elementary School Students - Sudaryono, Sudaryono; Aryani, Ine Kusuma (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
This research was conducted to find out, explore, study, and describe the implementation of disciplinary character education in elementary schools and expected to help find the right policies to support the successful implementation of character education. The type of data used is secondary data. This research uses the literature study method. The data obtained were collected, analyzed, and concluded obtain conclusions about the literature study. Based on the research results, literature studies from several research results and journal articles indicate that implementation school policies by establishing good cooperation between all school residents and school committees can increase the success of the implementation of character education in elementary schools.